Re-Defining Youth and Women Empowerment: Interogating the NAFA Program Initiative in The Gambia - Omotosho, Oyejide Felix; Abatan, Olajide Olusegun (Asian Business Research Journal, 2024)
With the extreme poverty level and its widespread in the Gambia as of 2012 and government’s concern to counter it, empowerment became one of the strategies to tackle the problem through social protection program, gazette as a policy for reduction of the shocks on the marginalized and the vulnerable. This study centered on the NAFA project-a quick cash transfers project mechanism and its execution in the Barrow administration to needy households in tackling poverty and hunger in the Gambia and towards empowering the perceived vulnerable women and youths in the Gambian communities. The study examined the execution of the scheme and its effectiveness by the government and the extent to which it had been used to adequately improve the poor conditions of women and the youths under the program. A descriptive research design with analytical approaches was employed to explore the objectives of the scheme in the pandemic era that people found it most difficult to earn living due to COVID-19 outbreak. Findings confirmed that NAFA scheme was relatively successful amidst inadequacies. The research advised on further reforms for a sustainable implemented NAFA scheme.